Analisis Penyerapan Tenaga Kerja Pada Transportasi Online di Kota Medan - Vina Maria Ompusunggu (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2018)
This research was conducted in the city of Medan, with the aim to find out how labor absorption in ojek transportation is online. This study uses qualitative data that aims to describe in detail and in depth about employment in online transportation. Data collection techniques used are by giving a list of questions and questionnaire forms and in-depth interviews. The population of this study is around 30 people and all of them are created as samples or total samples. The results of the study show that labor absorption in online transportation has absorbed labor from the urban population of the field is quite large. Based on data from BPS in 2017, 58.35% of the workforce is increasing and working in informal fields based on online transportation. This is due to several factors, including the existence of economic demands that can provide substantial amounts of income, a work system that is flexible, easy allocation of time, and a work system that facilitates work partners in IT-based services